Curriculum Management and Implementation Management at Madrasah Ibtidaiyah (Islamic Elementary School) Al Mukhlisin, Bandung - Elva Siti Fatimah; Yosep Farhan Dafik Sahal; Khusni Khusni; Mohamad Erihadiana (EDUTEC : Journal of Education And Technology, 2023)
The curriculum serves as a learning program to accomplish institutional goals in educational institutions, making it crucial in developing high-quality schools. Meanwhile, People are constantly condescending toward madrasah. The purpose of this study is to provide an overview of the planning and implementation of the curriculum at MI Al Mukhlisin, Bandung Regency. In this study, methods like documentation, interviews, and observation were used. In an effort to examine the data, data reduction techniques, data presentation, and conclusions are then used. According to the study's findings, students at MI Al Mukhlisin had to actively participate in their learning, and the curriculum there gave practical knowledge precedence over theoretical. The research suggestion in the study is the implementation of Kurrikulum Merdeka for Madrasah Ibtidaiyah ( Islamic Elementary School) in the future